2009
DOI: 10.1667/rr1679.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UMTS Cellular Phones on Human Hearing: Results of the European Project “EMFnEAR”

Abstract: The European project EMFnEAR was undertaken to assess potential changes in human auditory function after a short-term exposure to radiofrequency (RF) radiation produced by UMTS (Universal Mobile Telecommunication System) mobile phones. Participants were healthy young adults with no hearing or ear disorders. Auditory function was assessed immediately before and after exposure to radiofrequency radiation, and only the exposed ear was tested. Tests for the assessment of auditory function were hearing threshold le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Despite the fact that short-term exposure appears not to affect the human auditory system,43 audiological abnormality trends have recently been described 24 30…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that short-term exposure appears not to affect the human auditory system,43 audiological abnormality trends have recently been described 24 30…”
Section: Discussionmentioning
confidence: 99%
“…While several causes of hearing loss have been identified, including genetics, otitis media, certain prenatal and early‐life infections, injuries and prolonged exposure to loud noises, a recent review suggests that, for approximately 56% of hearing impaired children in the US, the cause is unknown . To date, experimental and non‐experimental studies have not provided solid evidence of effects of cell phones on auditory function . The only prospective study completed on this subject was of adults and found that cell phone users had a significant increase in average auditory threshold (evidence of hearing damage) at the end of 3 years of follow‐up compared with non‐users .…”
mentioning
confidence: 99%
“…A large sample size would be required to reach definitive conclusions. In contrast to the results of Panda et al (23), Parazzini et al (25) concluded that UMtS (Universal Mobile telecommunication System) short-term exposure at the maximum output of consumer mobile phones does not cause measurable immediate effects on the human auditory system (25).…”
Section: Resultsmentioning
confidence: 85%